The prevalence of overweight/obesity and its association with household food insecurity among women living with HIV in rural Eswatini - Nozipho Becker; Andile Mkhonta; Lindiwe N. Sibeko (BMC, 2022)
Abstract Background Eswatini is currently afflicted by an extremely high prevalence of HIV (27%) and malnutrition (both under-and over-nutrition). While rates of overweight/obesity in the general adult population have been documented, data on overweight/obesity and associated risk factors among women living with HIV (WLHIV) in Eswatini is limited. This study examines the prevalence of overweight/obesity and associated risk factors, with an emphasis on clarifying the association between household food insecurity and overweight/obesity for WLHIV in rural Eswatini. Methods This cross-sectional study was conducted among WLHIV (n = 166) in rural communities of Eswatini. Data were collected using an interviewer-administered survey questionnaire between October and November, 2017. Body Mass Index (BMI) was calculated to determine overweight and obesity among study participants. Women with BMI values of 25 kg/m2 or greater were classified as being overweight/obese. Multivariable log-binomial regression models were used to examine associations between household food insecurity and overweight/obesity in our study. Results Nearly a third (32.5%) of the women in our study were overweight and almost a quarter were obese (22.9%). We found significant associations between household food insecurity and overweight/obesity, with women who experienced household food insecurity the most being 0.38 times less likely to be overweight/obese compared to those who experienced household food insecurity the least (ARR: 0.38, 95% CI: 0.2-0.71). In our study sample, women who perceived themselves as being in poor health were less likely to be overweight/obese compared to those who perceived themselves as being in good health (ARR: 0.58, 95% CI: 0.39-0.86). We found significant associations between overweight/obesity and alcohol use, with the risk of overweight/obesity nearly 1.5 times higher among women who consumed alcohol compared to those who did not (ARR: 1.49, 95% CI: 1.07-2.05). Conclusions The high prevalence of overweight/obesity among food insecure women in poverty stricken communities may pose significant challenges for nutritional health and HIV management. With an increasing prevalence of overweight/obesity in food insecure households, there is a need to re-evaluate current strategies and develop multi-level targeted interventions that include prevention of excessive weight gain among women, particularly those living with HIV in rural Eswatini. HIV programs could include screening to identify individuals at risk for overweight/obesity in this population, and provide nutrition education for weight management for those individuals.